Effects of dietary conjugated linoleic acid on growth performance, tissue adipocytokine levels and lipid metabolism of grass carp. (8th August 2018) - Zou, Qi; Yang, Yan‐ou; Wei, Bang‐Hong; Yu, Deng‐hang; Chen, Lu; Zhou, Teng; Huang, Feng; Dong, Gui‐Fang
Abstract: A 65‐day growth trial was conducted to investigate the effects of dietary conjugated linoleic acid (CLA) on growth performance, tissue adipocytokine levels and lipid metabolism of grass carp. Seven isonitrogenous and isolipidic diets were formulated as follows: 0 (control), 5 (CLA5), 10 (CLA10), 15 (CLA15), 20 (CLA20), 25 (CLA25) and 30 (CLA30) g/kg CLA. Results showed that incorporating as low as 25 g/kg CLA in the diet significantly decreased the growth of grass carp. The liver lipid content in fish fed with CLA15 to CLA30 significantly decreased. The leptin and resistin levels in liver of fish fed with CLA5 to CLA30 diets significantly increased. The mRNA expression levels of fatty acid synthase (FAS) and triacylglycerol lipase (TGL) in liver of fish fed with CLA5 to CLA30 and CLA10 to CLA30 diets also significantly decreased, respectively. In summary, the lipid‐lowering effects in grass carp liver were induced by the supplementation of 15–20 g/kg CLA, but its growth remained unaffected. Moreover, the lipid‐lowering effects of CLA on grass carp could also be modulated both by adipocytokine levels and by the expression of genes involved in lipid metabolism in tissues.